2022
DOI: 10.1038/s41419-022-05255-0
|View full text |Cite
|
Sign up to set email alerts
|

MIIP functions as a novel ligand for ITGB3 to inhibit angiogenesis and tumorigenesis of triple-negative breast cancer

Abstract: Migration and invasion inhibitory protein (MIIP) has been identified as a tumor suppressor in various cancer types. Although MIIP is reported to exert tumor suppressive functions by repressing proliferation and metastasis of cancer cells, the detailed mechanism is poorly understood. In the present study, we found MIIP is a favorable indicator of prognosis in triple-negative breast cancer. MIIP could inhibit tumor angiogenesis, proliferation, and metastasis of triple-negative breast cancer cells in vivo and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Additionally, it could indirectly attack tumor cells by activating anti-tumor immune responses through its derived factors such as flagellar proteins, lipoproteins, and lipopolysaccharides (J. Chen et al 2021a , b ). As a regulator of migration and invasion, MIIP, functioning as a protein, actively engages in the remodeling of the tumor cell cytoskeleton, cellular adhesion, and modulation of signaling pathways (Gao et al 2022 ). EGFR, belonging to the receptor tyrosine kinase family, exhibits a close association between its aberrant expression and activation, and the genesis, progression, invasion, and metastasis of tumors (Voldborg et al 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it could indirectly attack tumor cells by activating anti-tumor immune responses through its derived factors such as flagellar proteins, lipoproteins, and lipopolysaccharides (J. Chen et al 2021a , b ). As a regulator of migration and invasion, MIIP, functioning as a protein, actively engages in the remodeling of the tumor cell cytoskeleton, cellular adhesion, and modulation of signaling pathways (Gao et al 2022 ). EGFR, belonging to the receptor tyrosine kinase family, exhibits a close association between its aberrant expression and activation, and the genesis, progression, invasion, and metastasis of tumors (Voldborg et al 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…With the improvement of modern whole genome sequencing, the gut microbiome in the body can be efficiently detected [ 15 ]. There also has research shown that the occurrence of tumors is directly related to the change in the intestinal microbiome, which causes the metabolites disordered in the body, and even stimulates tumor-related signaling pathways, directly inducing the formation of tumor cells [ 16 , 17 ]. So, biomarkers that alter gut microbiomes can be used as a standard to predict tumorigenesis or as an auxiliary means to diagnose tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…With the improvement of modern whole genome sequencing, the gut microbiome in the body can be efficiently detected [15]. There also has research shown that the occurrence of tumors is directly related to the change in intestinal microbiome, which causes the metabolites disordered in the body, and even stimulates tumor-related signaling pathways, directly inducing the formation of tumor cells [16,17]. So, biomarkers that alter gut microbiome can be used as a standard to predict tumorigenesis or as an auxiliary means to diagnose tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%